A method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method
Through hydrogen reduction-microwave strengthening consolidation method, the particle size distribution and consolidation process of spherical iron powder are optimized, and the problem of insufficient density of spherical iron powder in the existing technology is solved, and the preparation of spherical iron powder with high density and high fluidity is realized. Suitable for high-end powder metallurgy field.
Patent Information
- Application Number
- CN202411440567.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing spherical iron powder preparation technology is difficult to achieve high density. Conventional processes have problems with uneven heating heat field and hysteresis, resulting in poor internal consolidation effect and low density of spherical agglomerates.
Using hydrogen reduction-microwave reinforced consolidation method, the particle size distribution of spherical powder is optimized through ultra-fine grinding, combined with centrifugal spray drying and sieving grading, and further high-temperature consolidation is carried out in the microwave field to ensure uniform and dense solidification of spherical agglomerates. Knot.
High-density spherical iron powder was obtained, and its density characteristics were much higher than that of the atomized iron powder and conventional reduced iron powder with equal particle size and distribution. It is suitable for high-end powder metallurgy fields, such as injection molding and drill bit preparation.
Smart Images

Figure CN118951032B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing spherical iron powder, in particular to a method for producing high-density spherical iron powder by a hydrogen reduction-microwave enhanced consolidation method, and belongs to the technical field of ultrafine iron powder preparation. Background Art
[0002] Iron powder is an important raw material in the field of powder metallurgy. It is rich in variety and has many preparation processes. Among them, spherical iron powder has good fluidity and high bulk density. Compared with other sponge iron or electrolytic iron, it is more suitable for pressing and molding, conventional fields of powder metallurgy manufacturing, and advanced manufacturing processes such as additive manufacturing and injection molding. The preparation technologies of spherical iron powder mainly include carbonyl method and gas atomization method. The products prepared by these two methods have good sphericity, smooth particle surface morphology, concentrated particle size distribution, and low oxygen content, but do not have the characteristics of high bulk density. It is difficult to meet the needs of high-end products in terms of bulk density. It is urgent to develop a more suitable high-density spherical iron powder preparation technology.
[0003] The bulk density of particles is closely related to their microscopic morphology, particle size ratio, and internal structure of particles. A Chinese patent (publication number: CN116833417A) discloses a method for producing spherical iron powder by hydrogen reduction, wherein the iron oxide raw material is subjected to ultrafine wet grinding to obtain ultrafine particle slurry; the ultrafine particle slurry is spray-dried to obtain spherical agglomerates; the spherical agglomerates are subjected to hydrogen reduction at a temperature of 750-850°C to obtain a reduction product, and the reduction product is ultrasonically dispersed to obtain spherical iron powder. This method can obtain spherical iron powder by one-step high-temperature hydrogen reduction and consolidation of spherical agglomerates, but the surface of the obtained spherical iron powder product has some particles and void structures, and even iron whiskers will precipitate at higher temperatures to destroy the spherical morphology, thereby reducing the bulk density compared to spherical powders, and conventional electric heating methods still have problems of uneven heating thermal field and hysteresis, resulting in poor internal consolidation effect of spherical agglomerates and low density. Summary of the invention
[0004] In view of the defects and shortcomings of the prior art, the purpose of the present invention is to provide a method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation, which can obtain the characteristics of high sphericity, high density, high fluidity, etc. More specifically, the method can obtain high-density spherical iron powder by improving the sphericity of spherical powder, improving the particle size distribution of spherical powder, avoiding surface defects and crystal dendrites, and increasing internal dense consolidation. The density characteristics of spherical iron powder are much higher than those of atomized iron powder and conventional reduced iron powder with the same particle size and distribution, and can be widely used in the field of powder metallurgy including injection molding to prepare high-density bullets, drill bits and other products and related fields.
[0005] The high-density spherical iron powder of the present invention, "high density" means that the bulk density is greater than 4g / cm 3 above.
[0006] In order to achieve the above technical objectives, the present invention provides a method for producing high-density iron powder by hydrogen reduction-microwave enhanced consolidation method, the method comprising the following steps:
[0007] 1) Ultrafine grinding of the iron oxide raw material to obtain ultrafine particle slurry; wherein, in the ultrafine grinding process, three different particle size grinding beads with a particle size distribution in the range of 0.1~5mm are used, and 5≤R max / R small ≤10, R max is the diameter of the largest grinding bead, R small is the minimum diameter of grinding beads; the ultrafine grinding adopts high-energy ball milling or nano sand milling, and the ultrafine grinding conditions are: water or alcohol is used as the medium, the grinding beads are matched according to the mass ratio of large, medium and small particle sizes of 2-4:3-5:2-4, the grinding speed is 2000-4000r / min, and the grinding time is 1-3 hours;
[0008] 2) centrifugally spray drying the ultrafine particle slurry to obtain spherical agglomerates;
[0009] 3) screening and grading the spherical agglomerates and separating the spherical agglomerates with high specific gravity;
[0010] 4) placing the high specific gravity spherical agglomerates in a reduction furnace for low temperature hydrogen reduction at 475-600° C., and then placing them in a microwave reaction furnace for high temperature consolidation at 800-900° C. to obtain iron powder agglomerates;
[0011] 5) The iron powder agglomerates are broken up to obtain high-density iron powder.
[0012] The present invention improves the sphericity of spherical powders, improves the particle size distribution of spherical powders, avoids surface defects and dendrites, and increases internal dense consolidation, etc., so as to obtain high-density spherical iron powder. First of all, the present invention optimizes the process of ultrafine grinding. The key is to use grinding beads with special particle size distribution to realize the pretreatment of iron oxide raw materials, which can ensure that a certain fineness of granular materials is obtained, and the particle size distribution of the granular materials can be regulated, mainly to widen the particle size distribution range of the granular materials, thereby effectively avoiding the defect of a larger porosity caused by the accumulation of particles of the same particle size. Secondly, the centrifugal spray drying method is adopted to ensure that the granular materials maintain a higher cohesion force at the nozzle, so as to obtain spherical agglomerates with higher density. Thirdly, the spherical agglomerates are screened, graded and re-selected. Through screening and grading, particles of different particle sizes can be obtained, unqualified particle sizes can be removed, and subsequent re-selection is supported to remove unqualified particles of density such as hollow powder and defective powder. Finally, the high-density spherical agglomerates are further consolidated at high temperature in a microwave field after low-temperature hydrogen reduction. The advantage of microwave consolidation is that the spherical agglomerates are consolidated from the inside to the outside, and the unconsolidated fine particles have strong wave absorption capacity, and the relative absorption energy and temperature will be higher. The uniformity and density of the consolidated particles will be higher overall, and the energy utilization efficiency in the process will also be better. In summary, the present invention can obtain high-density spherical iron powder, and its density characteristics are much higher than those of atomized iron powder and conventional reduced iron powder of the same particle size and distribution, and can be used in the powder metallurgy field including injection molding to prepare high-density products such as high-density bullets and drill bits and related fields.
[0013] As a preferred solution, the iron oxide raw material includes at least one of super iron concentrate and iron scale. As a preferred solution, the mass content of non-oxygen impurities in the iron oxide raw material is not higher than 1%. The iron oxide raw material is mainly a high-purity iron oxide concentrate, and the total mass content of impurities other than oxygen does not exceed 1%. The iron oxide raw material is mainly an ore raw material or processed product for conventional metal smelting. In order to ensure the purity of the iron powder, the mass content of impurities in the raw material is controlled to be less than 1% from the source. Of course, the higher the purity of the iron oxide raw material, the purity of the prepared iron powder will also increase accordingly. The mass content of non-oxygen impurities in the iron oxide raw material is not higher than 1%, which can ensure that the purity of the iron powder product after reduction is greater than 98.5%.
[0014] Under the ultrafine grinding conditions of the present invention, the particle size D50 of the ultrafine particles in the ultrafine particle slurry can be ensured to be between 100 and 300 nm, and the particle distribution is relatively wide. 90 / D 10≥8. By selecting grinding beads of different sizes in the range of 0.1~5mm, a reasonable ratio of particle size can be achieved while achieving particle size refinement. Too high a grinding speed or too long a grinding time will lead to homogenization of the product particle size, while too low a grinding speed or too short a grinding time will not achieve the purpose of particle refinement, so it is necessary to control appropriate grinding conditions. The particle size of ultrafine particles is controlled at D50 between 100~300nm to ensure that the particles have sufficient reaction activity for hydrogen reduction and consolidation. The appropriate particle size distribution is D 90 / D 10 ≥8, more preferably 8≤D 90 / D 10 ≤15, by controlling the particle size distribution, the maximum packing density of the particles can be achieved as much as possible, and agglomerates with higher density can be obtained in the later spraying process.
[0015] As a preferred solution, the conditions of the centrifugal spray drying are: the solid content of the ultrafine particle slurry is 50-70%, the feed rate is 50-100 mL / min, the spray outlet temperature is 200-270°C, and the centrifugal speed is 30000-37000 r / min. Solid content is a conventional term, referring to the solid mass content. Since no binder, plasticizer, dispersant, antioxidant coating agent or other additives are added to the ultrafine particle slurry except the solvent, in order to avoid introducing new impurities and reducing the purity of the spherical iron powder, a considerable portion of larger particles (>1000nm) exist in the ultrafine particle slurry, and the deposition is more serious. By configuring the ultrafine particle slurry with a high solid content, it is possible to avoid the obvious stratification of large and small particles caused by too low solid content. At the same time, based on the high-speed centrifugal process of centrifugal spray drying, it is possible to ensure that the ultrafine particle slurry is highly evenly dispersed during the spraying process, which is conducive to obtaining spherical agglomerates with high-density accumulation of particles. The present invention can adjust the diameter of the spherical agglomerates to 15-53 μm and the bulk density to be greater than 1.7 g / cm by controlling the spray drying conditions, such as a feed rate of 50-100 mL / min, a spray outlet temperature of 200-270 ° C, and a centrifugal speed of 30000-37000 r / min. 3 In particular, the ultrafine particle slurry is a mixed slurry containing large and small particles, and its spraying is difficult. It is necessary to set the nozzle temperature above 200°C, and the temperature is further preferably 250~270°C. The centrifugal speed is further preferably 30000~37000r / min, which can achieve a density of 15~53µm spherical agglomerates formed by spraying before reduction and consolidation greater than 2.0g / cm 3 .
[0016] As a preferred solution, the screening and grading standard is D 90 / D 10The mass ratio is 1.7 to 2. The spherical agglomerates are screened to optimize the particle size ratio, and provide raw materials with uniform particle size for subsequent gravity sorting, and can also screen out some particles that have not been successfully sprayed.
[0017] As a preferred solution, the mass proportion of the low-density particles eliminated by the inertial sorting is 10% to 20%. The spherical agglomerates need to use the difference in inertial force between light and heavy particles to sort out particles with higher density. Different sorting machine parameters are set according to the different particle sizes after the above screening to screen out unqualified particles with a specific gravity lower than the corresponding level, and the proportion of lighter particles screened out is set to 10% to 20% of the total mass. The gravity sorting equipment is a dry gravity sedimentation classification equipment, a dry inertial classification equipment, and a wind classification equipment, etc., which realizes the gravity sorting of particles of the same size after screening, and further screens out unqualified hollow powder and powders with poor stacking and agglomeration and large porosity. The mass proportion of the low-density particles eliminated by the inertial sorting is further preferably 15% to 20%.
[0018] As a preferred solution, the cloth thickness of the high specific gravity spherical agglomerates in the low-temperature hydrogen reduction process is 2-5 mm, and the hydrogen reduction time is 3-5 h. Since the spherical agglomerates are very dense and have low porosity, hydrogen penetration is difficult and it is difficult to ensure the penetration depth at low temperatures. To ensure sufficient reduction, the reduction parameters are set to a cloth thickness of 2-5 mm, a reduction temperature of 475-600 ° C, and a reduction time of 3-5 h, wherein the reaction gas is set to hydrogen, accounting for more than 70% of the total gas.
[0019] As a preferred solution, a high-temperature tubular reactor or a push-boat reactor using microwaves is used in the high-temperature consolidation process, the heating rate does not exceed 50°C / min, and the high-temperature consolidation time is 10 to 30 minutes. Based on the selectivity of microwave heating, it has a better energy absorption and heating effect for the unconsolidated small particles and sharp surfaces of particles in the spherical agglomerates. During the consolidation process, energy can be better concentrated, the consolidation is tighter, the density and strength are higher, and in addition, the malignant sintering between the agglomerates is avoided, and the consolidation reaction is also faster. In the microwave consolidation process, the material temperature is controlled by infrared measurement and control, and the microwave power is adjusted to control the heating rate of the reduced material to not exceed 50°C / min. After consolidation, the material is naturally cooled in an inert atmosphere. Microwave heating has the characteristics of a fast heating rate, but in order to maintain the morphology and strength of the spherical agglomerates, the heating rate should not be greater than 50°C / min. After the microwave is removed, the cooling rate is very fast, and it can be quickly cooled in an inert atmosphere or a reaction atmosphere to avoid oxidation.
[0020] As a preferred solution, the dispersion is performed by air jet milling or ultrasonic method to disperse the agglomerated particles during the high temperature process. After consolidation, the iron powder will have agglomeration phenomenon, which needs to be dispersed by air jet milling or ultrasonic method.
[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0022] The present invention uses cheap iron oxide minerals as raw materials and adopts hydrogen reduction-microwave enhanced consolidation method to prepare spherical iron powder. The preparation process cost is lower than that of atomization method or carbonyl method, and does not require harsh reaction conditions such as high temperature and high pressure or the use of toxic reagents. The reaction process is green, clean and pollution-free, and the prepared product has the characteristics of high density.
[0023] The present invention controls the product particle size by regulating the slurry spraying and reduction-microwave enhanced consolidation process, and realizes the maximum packing density of the particles as much as possible by controlling the grinding particle size distribution. In the spraying process, higher centrifugal speed, temperature and other parameters matching the particle size are adopted to ensure that the particles maintain a higher agglomeration force at the nozzle, so as to obtain agglomerates with higher density, and further prepare spherical iron powder with higher density.
[0024] The present invention removes hollow powder, broken powder and other agglomerate particles with small specific gravity through screening, gravity sorting / inertial sorting, thereby solving the problem of uneven powder particles, so that the prepared spherical iron powder has a large loose density, and the uniformity and flowability of the particles are also improved, and the physical properties are greatly improved.
[0025] The present invention adopts microwave heating to carry out the consolidation process of the agglomerate, and adopts appropriate temperature rise and fall and consolidation process conditions. In the microwave heating process, the energy is selective, and the energy is more concentrated on the required unconsolidated parts, so the utilization efficiency is higher, the internal bonding of the spherical iron powder is more dense, and the rupture of the spheres or severe sintering between the spheres caused by uneven heating is avoided. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a morphology picture of the spherical iron powder prepared in Example 1.
[0027] Figure 2 This is the morphology of the spherical iron powder prepared in Example 2.
[0028] Figure 3 This is the morphology of the spherical iron powder prepared in Example 3.
[0029] Figure 4 This is a morphology picture of the spherical iron powder prepared in Comparative Example 1.
[0030] Figure 5 This is a morphology picture of the spherical iron powder prepared in Comparative Example 2. DETAILED DESCRIPTION
[0031] In order to more clearly understand the present invention, specific embodiments are now used to more clearly explain and analyze the contents of the present invention. However, the claims of the present invention are not limited to the following example methods and conditions. Other examples obtained by relevant technical personnel in the field without creative work are all within the protection scope of the present invention.
[0032] Example 1
[0033] The super iron concentrate obtained by deep beneficiation is selected as raw material, with an iron grade of 72.1% and the total content of other impurities (acid insoluble matter) of only 0.3%. The iron concentrate is finely ground in a nano sand mill, using the model XL-B10-B60 high-efficiency pin-type nano sand mill with a speed of 2500r / min. The grinding beads are 0.1mm, 0.5mm, and 1.0mm zirconium oxide balls, respectively, with a ball mass ratio of 3:4:3, ethanol as solvent, and a solid-liquid ratio of 1g:10mL. After 1 hour of grinding, an ultrafine particle slurry with a particle size of D50=300nm and D90 / D10=15 is obtained. The solid content of the ultrafine particle slurry is adjusted to 50% by sedimentation and then enters the spray drying system. The ultrafine particle slurry was dried in a centrifugal spray dryer, where the ultrafine particle slurry pumping rate was 100 mL / min, the nozzle temperature was 270 °C, and the sprayer speed was 37000 r / min. The diameter of the spherical agglomerates was about 40 μm and the bulk density was 2.0 g / cm 3 When screening, the sieves were set to 38μm and 45μm, the powder was divided into three groups, and 20% of the low-density spherical agglomerates were removed by gravity selection.
[0034] In the reduction stage of spherical agglomerates, the hydrogen reduction temperature was controlled at 475°C, the material height was 2mm, and pure hydrogen was introduced for 5h. After the reduction, it was placed in a microwave high-temperature tubular reactor and heated rapidly by microwave heating at a rate of 50°C / min. Argon was introduced at the same flow rate, and the microwave roasting temperature was controlled at 800°C. The roasting consolidation time was 10min. After the consolidation, the microwave was turned off, and the material was rapidly cooled in an argon atmosphere. The material layer was dispersed by an ultrasonic cell disperser in anhydrous ethanol. The ultrasonic power was set to 0.8kW / L, and the required dispersion time was about 3min. The subsequent detection of the loose density of the iron powder was 4.20 g / cm 3 , the iron powder morphology image is as follows Figure 1 As shown in the figure, it can be seen that the sphericity is good, the loose density is large, the surface is smooth without voids, and the comprehensive performance of the powder is good. Subsequently, the sphericity of the iron powder produced under this condition was calculated by image analysis software to be 99.21%.
[0035] Example 2
[0036] The raw material is steel scale produced in a certain place, with an iron grade of 72.4%. The main components are Fe2O3 and some Fe. The characteristics are that the content of other impurities such as Al, Mn, Si is relatively high, and the total amount of impurity elements is 1%. The material is also finely ground in a nano sand mill. The high-efficiency pin-type nano sand mill model XL-B10-B60 is selected, with a speed of 3000r / min. The grinding beads are 0.1mm, 0.3mm, and 0.5mm zirconium oxide balls, respectively, with a ball mass ratio of 1:1:1, water is used as the solvent, and the solid-liquid ratio is 1g:3mL. After three hours of grinding, an ultrafine particle slurry with a particle size of D50=100nm and D90 / D10=8 is obtained. The solid content of the ultrafine particle slurry is subsequently adjusted to 70% by sedimentation before entering the spray drying system. The ultrafine particle slurry was dried in a centrifugal spray dryer, where the ultrafine particle slurry pumping rate was 50 mL / min, the nozzle temperature was 250 °C, and the sprayer speed was 30000 r / min. The diameter of the spherical agglomerates was about 46 μm, and the finest particle was 18 μm. The bulk density was 1.7 g / cm 3 The particles were screened into two groups using a 45-micron sieve, and 10% of the low-density spherical agglomerates were removed by gravity selection.
[0037] During the reduction stage of the spherical agglomerates, the reduction temperature was controlled at 600°C, the material height was 5mm, and 70% hydrogen (the remaining gas was argon) was introduced for reduction for 3 hours. After the reduction was completed, it was placed in a microwave high-temperature tubular reactor and heated rapidly by microwave heating at a rate of 30°C / min. Argon was introduced at the same flow rate, and the microwave roasting temperature was controlled to be 900°C, and the roasting consolidation time was 30 minutes. After the consolidation was completed, the microwave was turned off, and the material layer was rapidly cooled in an argon atmosphere. It was placed in anhydrous ethanol and the material layer was dispersed by an ultrasonic cell disperser. The ultrasonic power was set to 0.8kW / L, and the required dispersion time was about 5 minutes. The subsequent detection of the loose density of the iron powder was 4.02g / cm 3 , the iron powder morphology image is as follows Figure 2 As shown in the figure, the sphericity of the iron powder produced under this condition is calculated to be 99.11%. Figure 2 It can be seen that it maintains a high degree of sphericity and smoothness, but the effect of refining the particle size ratio is relatively poor, and the gravity sorting fails to completely remove the light agglomerates. There are a small number of pores or cracks on the surface of the spheres under the electron microscope, and the loose density is slightly reduced.
[0038] Example 3
[0039] The super iron concentrate obtained by deep beneficiation is selected as raw material, with an iron grade of 72.1% and the total content of other impurities (acid insoluble matter) of only 0.3%. The iron concentrate is finely ground in a nano sand mill, using the model XL-B10-B60 high-efficiency pin-type nano sand mill with a speed of 4000r / min. The grinding beads are 0.5mm, 2mm, and 5mm zirconium oxide balls, respectively, with a ball mass ratio of 3:4:3, ethanol as solvent, and a solid-liquid ratio of 1g:5mL. After 1.5 hours of grinding, an ultrafine particle slurry with a particle size of D50=500nm and D90 / D10=13 is obtained. The solid content of the ultrafine particle slurry is subsequently adjusted to 50% by sedimentation before entering the spray drying system. The ultrafine particle slurry was dried in a centrifugal spray dryer, where the ultrafine particle slurry pumping rate was 50 mL / min, the nozzle temperature was 200 °C, and the sprayer speed was 35000 r / min. The diameter of the spherical agglomerates was about 45 μm and the bulk density was 1.9 g / cm 3 When screening, the sieves are set to 40μm and 50μm, the powder is divided into three groups, and 20% of low-density spherical agglomerates are screened out by gravity selection.
[0040] In the reduction stage of spherical agglomerates, the hydrogen reduction temperature was controlled at 575°C, the material height was 3mm, and pure hydrogen was introduced for 4h. After the reduction, it was placed in a microwave high-temperature tubular reactor and heated rapidly by microwave heating at a rate of 30°C / min. Argon gas was introduced at the same flow rate, and the microwave roasting temperature was controlled at 850°C. The roasting consolidation time was 20min. After the consolidation, the microwave was turned off, and the material was rapidly cooled in an argon atmosphere. The material layer was placed in anhydrous ethanol and dispersed by an ultrasonic cell disperser. The ultrasonic power was set to 0.8kW / L, and the required dispersion time was about 4min. The subsequent detection of the loose density of the iron powder was 4.15 g / cm 3 , the iron powder morphology image is as follows Figure 3 As shown in the figure, it can be seen that the iron powder has a high sphericity. Subsequent calculations using image analysis software show that the sphericity of the iron powder produced under this condition is 99.18%.
[0041] Comparative Example 1
[0042] This comparative example is used to illustrate the difference between the present invention using refined particle size ratio and gravity separation and not using them: the super iron concentrate obtained by deep ore dressing is selected as raw material, the iron grade is 72.1%, and the total content of other impurities (acid insoluble matter) is only 0.3%.
[0043] Similar to Example 1, the iron ore concentrate was finely ground in a nano sand mill. The model was XL-B10-B60 high-efficiency pin-type nano sand mill with a rotation speed of 2500 r / min. The grinding beads were 0.1 mm, 0.5 mm, and 1.0 mm zirconia balls, respectively, with a ball mass ratio of 3:4:3, ethanol was used as the solvent, and the solid-liquid ratio was 1 g:10 mL. After 1 hour of grinding, an ultrafine particle slurry with a particle size of D50 = 300 nm and D90 / D10 = 15 was obtained.
[0044] The ethanol content of the slurry was subsequently adjusted to 50% by sedimentation and then entered the spray drying system. The slurry was dried in a centrifugal spray dryer to obtain a powder, wherein the slurry pumping rate was 100 mL / min, the nozzle temperature was 270°C, and the sprayer speed was 37000 r / min. The diameter of the agglomerates obtained was about 40 μm, and the bulk density was 2.0 g / cm 3 .
[0045] The hydrogen reduction-microwave enhanced consolidation stage was the same as in Example 1. The subsequent detection of the iron powder bulk density was 3.87 g / cm 3 , the bulk density is relatively reduced, and the iron powder morphology image is as follows Figure 4 As shown, it is calculated that the sphericity of the iron powder produced under this condition is 98.96%, which is different from the present invention which adopts the method of refined particle size ratio and gravity separation. The spherical iron powder prepared by the present invention contains some unqualified powders such as broken fine powder, the bulk density is reduced, and the process performance is poor.
[0046] Comparative Example 2
[0047] Compared with Example 2, the only difference is that electric heating consolidation is used. Specifically, after the spherical agglomerates are reduced, the temperature is raised to 900°C at 30°C / min by electric heating, the reduced iron powder is placed on a reduction steel belt, an argon atmosphere is introduced, and the roasting consolidation time is 60 minutes. After the consolidation is completed, the electric heating is turned off, and the mixture is slowly cooled in an argon atmosphere.
[0048] Subsequent testing showed that the bulk density of spherical iron powder was 3.86 g / cm 3 , the bulk density is relatively low, and the morphology of spherical iron powder is as follows Figure 5 As shown in the figure, the spherical iron powder obtained by electric heating consolidation has some mesoporous structures on its surface, which causes the macroscopic packing density to decrease, resulting in poor product performance, indicating that it is difficult to achieve sufficient surface consolidation by electric heating. Subsequent calculations show that the sphericity of the iron powder produced under this condition is 98.24%.
Claims
1. A method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method, characterized in that: The following steps are involved: 1) Ultrafine grinding of the iron oxide raw material to obtain ultrafine particle slurry; wherein, in the ultrafine grinding process, three different particle size grinding beads with a particle size distribution in the range of 0.1~5mm are used, and 5≤R max / R small ≤10, R max is the diameter of the largest grinding bead, R small is the minimum diameter of grinding beads; the ultrafine grinding adopts high-energy ball milling or nano sand milling, and the ultrafine grinding conditions are: water or alcohol is used as the medium, the grinding beads are matched according to the mass ratio of large, medium and small particle sizes of 2-4:3-5:2-4, the grinding speed is 2000-4000r / min, and the grinding time is 1-3 hours; 2) centrifugally spray drying the ultrafine particle slurry to obtain spherical agglomerates; 3) screening and grading the spherical agglomerates and separating the spherical agglomerates with high specific gravity; 4) placing the high specific gravity spherical agglomerates in a reduction furnace for low temperature hydrogen reduction at 475-600° C., and then placing them in a microwave reaction furnace for high temperature consolidation at 800-900° C. to obtain iron powder agglomerates; 5) The iron powder agglomerates are broken up to obtain high-density iron powder.
2. The method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method according to claim 1, characterized in that: The iron oxide raw material includes at least one of super iron concentrate and iron scale; The mass content of non-oxygen impurities in the iron oxide raw material is not higher than 1%.
3. The method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method according to claim 1, characterized in that: The conditions of the centrifugal spray drying are: the solid content of the ultrafine particle slurry is 50-70%, the feed rate is 50-100 mL / min, the spray outlet temperature is 200-270° C., and the centrifugal speed is 30000-37000 r / min.
4. The method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method according to claim 1, characterized in that: The screening and grading standard is D 90 / D 10 The mass ratio is 1.7~2.
5. The method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method according to claim 1, characterized in that: The eliminated mass of low-density particles by inertial sorting accounts for 10% to 20%.
6. The method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method according to claim 1, characterized in that: The thickness of the high specific gravity spherical agglomerates during the low-temperature hydrogen reduction process is 2-5 mm, and the hydrogen reduction time is 3-5 h.
7. The method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method according to claim 1, characterized in that: The high-temperature consolidation process adopts a high-temperature tubular reactor or a pusher boat reactor heated by microwaves, the heating rate does not exceed 50° C. / min, and the high-temperature consolidation time is 10 to 30 minutes.
8. The method for producing high-density spherical iron powder by hydrogen reduction-microwave enhanced consolidation method according to claim 1, 2, 4, 5, 6 or 7, characterized in that: The breaking up is carried out by air jet milling or ultrasonic grinding.
